PREVENTION OF WATER POLLUTION CAUSED BY NITRATES FROM AGRICULTURE IN SERBIA - Vuković, Predrag; Popović, Vesna; Subić, Jonel; Kljajić, Nataša (Economics of Agriculture, 2018)
Knowledge of agricultural soil vulnerability to water and nitrogen losses is essential for designing management guidelines to minimize water pollution from agriculture. Here, the authors presented the results of assessing the intrinsic vulnerability of agricultural soil of the City of Pančevo (Serbia) to water and nitrogen losses using LOS indices method. As the most vulnerable, the indices, presented in the form of vulnerability maps, marked the northeast part of the City of Pančevo area, including part of Deliblato Sands. Determined closed periods for use of fertilizers, rules for soil application and balanced fertilization, optimized production structure and irrigation methods, application of contour ploughing and conservation tillage and maintenance of buffer strips are among the priority nitrogen best management practices (BMPs) for agriculture and water protection. Well-tailored, site-specific nitrogen BMPs based on the LOS analysis can significantly improve compliance with EU Nitrate Directive, which transposition is ongoing in Serbia.